Rhizoma polygonati from Mount Tai: nutritional value and usefulness as a traditional Chinese medicine, source of herbzyme, and potential remediating agent for COVID-19 and chronic and hidden hunger. Issue 1 (September 2021) - Nurtay, Lazzat; Sun, Qinglei; Mu, Chenglin; Cao, Zhongshan; Wang, Qian; Liang, Zongsuo; Ma, Cuiping; Li, Xugang; Amin, Amr; Xie, Yingqiu
Abstract : Abstract: Recently, traditional Chinese medicine-based treatment has succeeded in fighting coronavirus disease 2019 (COVID-19), and Rhizoma polygonati (Huangjing) has been one of the recommended components. Its processed products play antidiabetic, antiviral, antitumor, antioxidation, antifatigue, antiaging, and immune enhancement roles. The climate in Mount Tai is mild, and the dense forest is suitable for the growth of Rhizome polygonati, which has gradually evolved into a unique specie. Considering the important medicinal value and pleasant taste of Mount Tai- Rhizoma polygonati, various healthy and functional food products, controlled by quality markers with anti-COVID-19 potential, as well as emergency foods can be developed. The study aimed to review current evidence on the nutritional value of Rhizoma polygonati from Mount Tai and its usefulness as a traditional Chinese medicine, source of herbzyme, and potential remediating agent for COVID-19 and food shortage. Most recent findings regarding herbal nanomedicine have revealed that nanoscale chemical compounds are potentially efficient in drug delivery or nanozyme catalysis upon bioprocessing. Nanoflower structure is found in processed Rhizoma polygonati by self-assembly and has wide application in enzymatic events, particularly nanoscale herbzyme. The novel findings regarding Mount Tai- Rhizoma polygonati could enhance its novel applications in chronic and hidden hunger, clinical nanomedicine, and as an anti-COVID-19 agent.